Motivation of collegiate football coaches during COVID-19 pandemic - Ube, Alyssa Jane A. 1998-; Guinto, Maria Luisa M. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2021)
During the COVID-19 pandemic, sports like football experienced a radical shift in their environment from face-to-face to virtual or remote. Coaches had to innovate to keep their athletes motivated and engaged with the sport to ensure the continued development of their athletes despite restrictions. However, related literature on coaches mainly was about how their behaviors affect athletes; very few focuses on what drives them or motivates coaches. While most of the research on motivation in sport focuses on the athletes, only few studies have examined coaches' experience. The primary purpose of this qualitative research was to investigate the motivation of the football cpaches during the COVID-19 pandemic using Self-Determination Theory (SDT), focusing on the three basic psychological needs: autonomy, competence, and relatedness. The participants were four caoches from the five participating UAAP women's football teams, coaching the team years before the pandemic. Thematic analysis of data was conducted using and inductive method. Player's development, connection with the players, support from the school, and challenges were identified as themes. These themes were found to satisfy their need for autonomy, competence, and relatedness which motivates the coaches during this pandemic.
Vita.
Thesis
Keywords: COVID-19 pandemic; Football coaches -- Philippines -- Physiological aspects